(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2004)
Modernism in architecture always has a concrete, profane and clear concept.On the totally contrary, traditional architecture traditional has an abstract, spiritual and often religious concept or way of thinking. Toraja, an ethnic group in the northern part of South Sulawesi, has a beautiful and unique architecture which is the expression of Aluk Todolo their way of life and religion. The cosmological thinking of Aluk Todolo is expressed in the architecture of Toraja through it’s site plan and units orientation, construction, orientation, material, detail, ornament and other architectural aspects. This article summarises the results of researches, seminars and bibliographical studies on the architecture of Toraja,conducted in the department of architecture University of Hasanuddin Makassar cases from three traditional villages (desa adat): Palawa a big traditional village, Ketekesu’ one of the most beautiful traditional villages and Siguntu represent a small desa adat, represent the Toraja traditional architecture. Abstract in Bahasa Indonesia : Modernisme dalam arsitektur selalu menunjuk pada hal-hal yang bersifat konkrit, profan dan konsep yang jelas. Sebaliknya tradisional seperti arsitektur tradisional menunjuk pada hal-hal yang bersifat abstrak, spiritual dan bahkan konsep religius atau "way of thinking". Toraja, sebuah kelompok etnik yang tinggal disebelah utara propinsi Sulawesi Selatan, mempunyai bentuk arsitektur tradisional yang unik dan indah, yang merupakan ekspresi dari "Aluk Todolo", agama dan "way of life" nya. Pemikiran kosmologi dan "Aluk Todolo" diekspresikan dalam arsitektur Toraja, baik dalam tata letak ( site plan), orientasi, konstruksi, material bangunan, detail, ornamen dan aspek-aspek arsitektur lainnya. Tulisan ini merupakan hasil ringkasan dari riset, seminar dan studi kepustakaan arsitektur Toraja, yang dilakukan oleh jurusan arsitektur Universitas Hasanuddin, Makasar di tiga desa adat. Palawa (desa tradisional yang besar), Ketekesu (sebuah desa adat yang indah) dan Siguntu (desa adat yang kecil tapi mempunyai banyak bangunan arsitektur tradisional Toraja). Kata kunci: Arsitektur Tradidional, Toraja.